MPC-informed ECMS based real-time power management strategy for hybrid electric ship. (April 2021) - Xie, Peilin; Tan, Sen; Guerrero, Josep M.; Vasquez, Juan C.
Abstract: Shipboard power systems (SPS) are complex systems connecting multiple power sources, energy storage systems (ESSs) and various types of loads. However, the fluctuated propulsion loads may lead to a low power quality of the system. In this paper, a power management system (PMS) is designed for SPS in the framework of an optimization-based method. With equivalent consumption minimization strategy (ECMS), the proposed method is able to provide an optimal power-split between hybrid energy sources in real time, while minimizing the fuel consumption of the system. Furthermore, the equivalence factor is adjusted by model predictive control (MPC) of PMS. The performances of the proposed approach are evaluated by simulations.